Anti-bonding master batch as well as preparation process and application thereof
By modifying the silicon micropowder and introducing a thermoplastic resin system to form a crosslinked structure, the problem of high surface roughness and poor anti-adhesion performance of release base film for MLCC is solved, ultra-low surface roughness and excellent anti-adhesion performance are achieved, and the preparation needs of high-end multi-layer ceramic capacitors are met.
Patent Information
- Application Number
- CN202510105404.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing release base film for MLCC has high surface roughness, poor anti-stick performance and poor heat resistance, making it difficult to meet the needs of high capacitance value and miniaturization technology.
The silicon micropowder is modified by using silane coupling agent and two-terminal carboxyl-terminated dimethylsiloxane, and the modified silicon micropowder is introduced into the thermoplastic resin system. The carboxylic acid groups in the polydimethylsiloxane molecular chain increase the interaction force between molecules to form a crosslinked structure, thereby improving the thermal stability and mechanical strength of the material.
It achieves ultra-low surface roughness (≤20nm) and excellent anti-tack performance, improves the heat resistance and mechanical strength of the film, and meets the preparation needs of the new generation of high-end multi-layer ceramic capacitors.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of BOPET films, in particular to an anti-adhesion masterbatch and a preparation process and application thereof. Background Art
[0002] Biaxially oriented polyethylene terephthalate film (BOPET) is widely used in printing, electronics, film and television, and photovoltaic industries. BOPET release film is a key material for the preparation of multilayer ceramic capacitors (MLCC). The rapid development of MLCC has driven a huge market demand for release film for MLCC, and at the same time, the demand for high-precision anti-adhesive masterbatch for MLCC release film has brought huge opportunities and challenges. Among them, the technical level of high-precision anti-adhesive masterbatch for MLCC release film is the key to MLCC release film. Therefore, the research and development and industrialization of anti-adhesive masterbatch for MLCC release film has great strategic significance and broad market prospects.
[0003] During the entire MLCC process, the release film is the carrier and high consumable of the ceramic sheet. Its smoothness, peelability and uniform thickness will ensure that it can be easily peeled off after drying without damaging the dielectric layer, so that it can be used for subsequent MLCC stacking. The domestic multilayer ceramic capacitor release base film currently used generally has problems such as high surface roughness, poor anti-sticking performance, and poor heat resistance, which makes it difficult to slit and unwind the release base film, poor surface flatness, and high thermal shrinkage, which in turn affects the thickness and surface roughness of the ceramic sheet, making it difficult to meet the requirements of high capacitance and miniaturization technology of MLCC. The particle size of the anti-sticking masterbatch used for conventional polyester film is micron-sized, and the surface roughness of the film is generally 40-80nm. In order to meet the production and high performance of ultra-thin ceramic capacitor sheets, the surface roughness of the base film is required to be ≤30nm, preferably 20nm, or even 10nm. For example, a Chinese patent application (publication number CN117844003A) discloses a functional masterbatch for MLCC film and a preparation method thereof. The method mainly reduces the roughness of the subsequent release film by etching and grafting modification of nano-silicon dioxide to obtain a smoother surface. However, if the roughness is too low, the winding and unwinding of the film preparation and application process will face huge challenges. Summary of the invention
[0004] In order to solve the above problems, the present invention provides an anti-sticking masterbatch with ultra-low surface roughness and excellent anti-sticking performance for preparing a release base film for MLCC, reducing the surface roughness of the film (≤20nm), and improving the film's anti-sticking, heat resistance and other performance indicators, thereby meeting the preparation needs of a new generation of high-end multilayer ceramic capacitors.
[0005] On one hand, the present invention provides an anti-sticking masterbatch, wherein the raw materials for its preparation include at least 90-100 parts of thermoplastic resin and 1-10 parts of modified silicon micropowder, wherein the modified silicon micropowder is silicon micropowder modified with a silane coupling agent and dimethylsiloxane capped with carboxyl groups at both ends.
[0006] As a preferred technical solution, the thermoplastic resin is at least one of PET, PETG, and PBT.
[0007] As a preferred technical solution, the modified silicon micropowder is spherical, and the particle size of the modified silicon micropowder ranges from 20nm to 500nm, preferably from 80nm to 180nm.
[0008] As a preferred technical solution, the bulk density of the modified silicon micropowder is 400 g / 100 mL to 1100 g / 100 mL, and the refractive index of the modified silicon micropowder is 1.40 to 1.55.
[0009] As a preferred technical solution, the true density of the modified silicon micropowder is 2.0 g / mL to 2.65 g / mL.
[0010] As a preferred technical solution, the method for preparing the modified silicon micropowder comprises the following steps:
[0011] The modified silicon micropowder is prepared by mixing a silane coupling agent, silicon micropowder, dimethylsiloxane capped with carboxyl groups at both ends and an ethanol aqueous solution, and heating and refluxing the mixture.
[0012] As a preferred technical solution, the silane coupling agent is at least one of vinyl triethoxy silane, vinyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane, and β-methoxyethoxy silane.
[0013] As a preferred technical solution, the silicon micropowder is spherical, with an average particle size of 10nm-400nm, preferably 50nm-150nm, most preferably 100nm, model KE-P10, and is sourced from Nippon Shokubai Co., Ltd.
[0014] As a preferred technical solution, the mass proportion of the silane coupling agent to the silicon micropowder is 1%-6%, preferably 4%-6%.
[0015] As a preferred technical solution, the mass proportion of the dimethylsiloxane terminated with carboxyl groups at both ends relative to the silicon micropowder is 2%-5%, preferably 2%-4%.
[0016] As a preferred technical solution, the ratio of the mass of the silicon micropowder to the volume of the ethanol aqueous solution is (5-20) g:100 mL, preferably (10-15) g:100 mL.
[0017] As a preferred technical solution, in the ethanol aqueous solution, the volume fraction of ethanol is 90% to 98%;
[0018] As a preferred technical solution, the temperature of the heating reflux reaction is 90°C to 100°C;
[0019] As a preferred technical solution, the heating reflux reaction time is 2h to 3h;
[0020] As a preferred technical solution, the heating reflux reaction is carried out under stirring, and the stirring speed is 300r / min to 450r / min.
[0021] As a preferred technical solution, after the heating reflux reaction is completed, the mixture is filtered and washed repeatedly with deionized water and anhydrous ethanol, and then placed in an oven at 100° C.-150° C. and dried for 8 h-16 h to obtain the modified silicon micropowder.
[0022] The present invention uses a silane coupling agent and two-terminal carboxyl-terminated dimethylsiloxane to modify silicon micropowder and then introduces it into a thermoplastic resin system. The carboxylic acid group in the polydimethylsiloxane molecular chain can increase the interaction force between molecules to form a cross-linked structure, thereby improving the thermal stability and mechanical strength of the material, so that it has better performance in high-temperature environments.
[0023] On the other hand, the present invention provides a process for preparing an anti-sticking masterbatch, which comprises at least the following steps: adding a thermoplastic resin and modified silicon micropowder into a twin-screw extruder for mixing and extruding granulation, air-cooling the obtained material, and then entering a granulator for granulation.
[0024] As a preferred technical solution, the preparation process of the anti-sticking masterbatch includes the following steps: adding a thermoplastic resin into a twin-screw extruder, heating it to 250°C-290°C, and performing melt shearing at a high speed of 350r / min-450r / min; adding modified silicon micropowder into the twin-screw extruder by side feeding, melt blending at 250°C-290°C, extruding and granulating the material, air cooling it, and then entering a pelletizer for pelletizing.
[0025] A third aspect of the present invention provides an application of an anti-sticking masterbatch, which is applied to the preparation of a BOPET temperature-resistant and stiffening film, wherein the mass proportion of the anti-sticking masterbatch in the BOPET temperature-resistant and stiffening film is 1%-10%, preferably 3%-7%.
[0026] As a preferred technical solution, the preparation method of the BOPET temperature-resistant and rigidified film is as follows: PET resin and anti-adhesive masterbatch are extruded by an extruder, and after cooling the cast sheet, longitudinal stretching and transverse stretching are sequentially performed, and the BOPET temperature-resistant and rigidified film is obtained after shaping, cooling and winding.
[0027] Preferably, the preparation method of the BOPET temperature-resistant and rigidified film is as follows: PET resin and anti-adhesive masterbatch are dropped into a surface extruder through a loss-in-weight scale, melt-filtered at a temperature of 280°C and then extruded from a die, cast on a cooling roller at a temperature of 26°C, preheated longitudinally at a preheating temperature of 70°C-90°C and stretched 3.5 times in the stretching section, cooled to 50°C in the cooling section, and then enters the transverse stretching preheating and transverse stretching box, with a preheating temperature of 90°C, a transverse stretching temperature of 100°C, and a stretching section of 3.5 times, and then set in a heat setting section at a temperature of 225°C, cooled and rolled up to obtain the BOPET temperature-resistant and rigidified film.
[0028] The film prepared using the masterbatch of the present invention has good anti-sticking properties and still has ultra-low surface roughness after high temperature, which will ensure that the release base film has excellent properties such as easy slitting and unwinding, high surface flatness, and low thermal shrinkage, thereby meeting the needs of MLCC high capacitance value and miniaturization technology.
[0029] The anti-sticking masterbatch provided by the present invention is added in the BOPET release base film system at 3wt%-7wt%. The prepared BOPET temperature-resistant and rigidified film has lower haze, adhesion roughness and thermal shrinkage, meets the subsequent multi-layer ceramic capacitor (MLCC) stacking use requirements, and has extremely high market promotion value.
[0030] Beneficial Effects
[0031] 1. The present invention provides an anti-sticking masterbatch with ultra-low surface roughness and excellent anti-sticking performance for preparing a release base film for MLCC, which reduces the surface roughness of the film (≤20nm), improves the film's anti-sticking, heat resistance and other performance indicators, thereby meeting the preparation needs of a new generation of high-end multilayer ceramic capacitors.
[0032] 2. The present invention uses a silane coupling agent and dimethylsiloxane with carboxyl groups at both ends to modify silicon micropowder and then introduces it into a thermoplastic resin system. The carboxylic acid group in the polydimethylsiloxane molecular chain can increase the interaction force between molecules and form a cross-linked structure, thereby improving the thermal stability and mechanical strength of the material, making it have better performance in high temperature environments.
[0033] 3. The film prepared using the masterbatch of the present invention has good anti-sticking properties and still has ultra-low surface roughness after high temperature, which will ensure that the release base film has excellent properties such as easy slitting and unwinding, high surface flatness, and low thermal shrinkage, thereby meeting the needs of MLCC high capacitance and miniaturization technology.
[0034] 4. The anti-sticking masterbatch provided by the present invention is added to the BOPET release base film system at 3wt%-7wt%. The obtained BOPET temperature-resistant and rigidified film has lower haze, adhesion roughness and thermal shrinkage, which meets the subsequent multi-layer ceramic capacitor (MLCC) stacking use requirements and has extremely high market promotion value. DETAILED DESCRIPTION
[0035] Example 1
[0036] On the one hand, Example 1 of the present invention provides an anti-sticking masterbatch, and its preparation raw materials include, by weight: 95 parts of thermoplastic resin and 5 parts of modified silicon micropowder, wherein the modified silicon micropowder is silicon micropowder modified with silane coupling agent and dimethylsiloxane capped with carboxyl groups at both ends.
[0037] The thermoplastic resin is PET with a brand name of FG600, purchased from Sinopec Yizheng Chemical Fiber Co., Ltd.
[0038] The modified silicon micropowder is spherical, and the particle size of the modified silicon micropowder ranges from 80nm to 180nm.
[0039] The bulk density of the modified silicon micropowder is 400 g / 100 mL to 1100 g / 100 mL, and the refractive index of the modified silicon micropowder is 1.40 to 1.55.
[0040] The true density of the modified silicon micropowder is 2.0 g / mL to 2.65 g / mL.
[0041] The preparation method of the modified silicon micropowder comprises the following steps: mixing a silane coupling agent, silicon micropowder, dimethylsiloxane capped with carboxyl groups at both ends and an ethanol aqueous solution, and performing a heating reflux reaction to prepare the modified silicon micropowder.
[0042] The silane coupling agent is vinyl triethoxysilane (KH-151), purchased from Nanjing Jingtianwei Chemical Co., Ltd., with the product number A-151.
[0043] The silicon micropowder is spherical, has an average particle size of 100 nm, is of model KE-P10, and is sourced from Nippon Shokubai Co., Ltd.
[0044] The mass proportion of the silane coupling agent to the silicon micropowder is 4%.
[0045] The mass proportion of the two-terminal carboxyl-terminated dimethylsiloxane to the silicon micropowder is 2.24%, and it is purchased from Hubei Nona Technology Co., Ltd.
[0046] The ratio of the mass of the silicon micropowder to the volume of the ethanol aqueous solution is 12.50 g:100 mL.
[0047] In the ethanol aqueous solution, the volume fraction of ethanol is 95%;
[0048] The temperature of the heating reflux reaction is 100°C;
[0049] The heating reflux reaction time is 3h;
[0050] The heating reflux reaction is carried out under stirring, and the stirring speed is 400r / min.
[0051] After the heating reflux reaction is completed, the mixture is filtered and washed repeatedly with deionized water and anhydrous ethanol, and then placed in an oven at 120° C. and dried for 12 hours to obtain the modified silicon micropowder.
[0052] On the other hand, Example 1 of the present invention provides a preparation process of an anti-sticking masterbatch, comprising the following steps: adding a thermoplastic resin into a twin-screw extruder, heating it to 260°C, and performing melt shearing at a high speed of 400 r / min; adding modified silicon micropowder into the twin-screw extruder by side feeding, melt blending at 280°C, extruding and granulating the material, air-cooling it, and then entering a pelletizer for pelletizing.
[0053] Example 2
[0054] Example 2 of the present invention provides an anti-sticking masterbatch and a preparation process thereof, and its specific implementation manner is the same as that of Example 1, except that the mass proportion of the silane coupling agent to the silicon micropowder is 5%.
[0055] Example 3
[0056] Example 3 of the present invention provides an anti-sticking masterbatch and a preparation process thereof, and its specific implementation manner is the same as that of Example 1, except that the mass proportion of the silane coupling agent to the silicon micropowder is 6%.
[0057] Comparative Example 1
[0058] Comparative Example 1 of the present invention provides an anti-sticking masterbatch and a preparation process thereof, and its specific implementation manner is the same as that of Example 1, except that the modified silicon micropowder is replaced by silicon dioxide purchased from Grace Company of the United States with a brand name of SYLOBLOC 35.
[0059] Comparative Example 2
[0060] Comparative Example 2 of the present invention provides an anti-sticking masterbatch and a preparation process thereof, and its specific implementation manner is the same as that of Example 2, except that the modified silicon micropowder is silicon micropowder modified by a silane coupling agent.
[0061] Comparative Example 3
[0062] Comparative Example 3 of the present invention provides an anti-sticking masterbatch and a preparation process thereof, and its specific implementation manner is the same as that of Example 2, except that the silicon micropowder is not modified (the modified silicon micropowder is replaced with silicon micropowder).
[0063] Application Examples 1-3, Application Comparative Examples 1-3
[0064] Application Examples 1-3 and Application Comparative Examples 1-3 of the present invention provide a BOPET temperature-resistant and rigidity-increasing film, and the formula is shown in Table 1 in parts by weight.
[0065] Table 1
[0066]
[0067] The preparation method of the BOPET temperature-resistant and rigidified film is as follows: according to Table 1, PET resin and anti-adhesive masterbatch are dropped into a surface extruder through a weight loss scale, melt filtered at a temperature of 280° C. and then extruded from a die head, cast on a cooling roller at a temperature of 26° C., preheated longitudinally at a preheating temperature of 70° C.-90° C. and stretched 3.5 times in a stretching section, cooled to 50° C. in a cooling section, and then enters a transverse stretching preheating and transverse stretching box, with a preheating temperature of 90° C., a transverse stretching temperature of 100° C., and stretched 3.5 times in the stretching section, and then fixed in a heat setting section at a temperature of 225° C., cooled and rolled up to obtain the BOPET temperature-resistant and rigidified film.
[0068] Performance Testing
[0069] 1. The BOPET temperature-resistant and rigidity-increasing films provided in the application examples and comparative examples were subjected to the performance tests shown in Table 2. The test methods and test results are shown in Table 2.
[0070] Table 2
[0071]
Claims
1. An anti-adhesive masterbatch, characterized in that: The raw materials for its preparation include at least 90-100 parts of thermoplastic resin and 1-10 parts of modified silicon micropowder by weight. The modified silicon micropowder is silicon micropowder modified by silane coupling agent and dimethylsiloxane capped with carboxyl groups at both ends.
2. The anti-sticking masterbatch according to claim 1, characterized in that: The thermoplastic resin is at least one of PET, PETG and PBT.
3. The anti-sticking masterbatch according to claim 1, characterized in that: The modified silicon micropowder is spherical, and the particle size of the modified silicon micropowder ranges from 20nm to 500nm.
4. The anti-sticking masterbatch according to claim 1, characterized in that: The bulk density of the modified silicon micropowder is 400 g / 100 mL to 1100 g / 100 mL, and the refractive index of the modified silicon micropowder is 1.40 to 1.
55.
5. The anti-sticking masterbatch according to claim 1, characterized in that: The true density of the modified silicon micropowder is 2.0 g / mL to 2.65 g / mL.
6. The anti-sticking masterbatch according to claim 1, characterized in that: The preparation method of the modified silicon micropowder comprises the following steps: mixing a silane coupling agent, silicon micropowder, dimethylsiloxane capped with carboxyl groups at both ends and an ethanol aqueous solution, and performing a heating reflux reaction to prepare the modified silicon micropowder.
7. The anti-sticking masterbatch according to claim 6, characterized in that: The silane coupling agent is at least one of vinyl triethoxy silane, vinyl trimethoxy silane, γ-glycidyl ether oxypropyl trimethoxy silane and β-methoxyethoxy silane.
8. The anti-sticking masterbatch according to claim 6, characterized in that: The silicon micropowder is spherical and has an average particle size of 10nm-400nm.
9. A process for preparing the anti-sticking masterbatch according to any one of claims 1 to 8, characterized in that: At least the following steps are included: Thermoplastic resin and modified silicon powder are added into a twin-screw extruder for mixing and extrusion granulation. The obtained material is air-cooled and then enters a pelletizer for pelletizing.
10. An application of the anti-sticking masterbatch according to any one of claims 1 to 8, characterized in that: The method is applied to the preparation of a BOPET temperature-resistant and rigidity-increasing film, wherein the mass proportion of the anti-adhesive masterbatch in the BOPET temperature-resistant and rigidity-increasing film is 1%-10%.
Citation Information
Patent Citations
Functional master batch for MLCC film and preparation method of functional master batch
CN117844003A
Special low-friction-coefficient anti-bonding master batch for BOPE (biaxially-oriented polyethylene) composite film, preparation method of master batch and BOPE composite film
CN115044125A
Anti-bonding master batch for release base film of multilayer chip ceramic capacitor and preparation process of anti-bonding master batch
CN117285806A